2013
DOI: 10.1016/j.febslet.2013.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate increases Nur77 expression by modulating ZBP89 and Sp1 binding to the Nur77 proximal promoter in pancreatic β‐cells

Abstract: Nur77 is a stress sensor in pancreatic β-cells, which negatively regulates glucose-stimulated insulin secretion. We recently showed that a lipotoxic shock caused by exposure of β-cells to the saturated fatty acid palmitate strongly increases Nur77 expression. Here, using dual luciferase reporter assays and Nur77 promoter deletion constructs, we identified a regulatory cassette between -1534 and -1512 bp upstream from the translational start site mediating Nur77 promoter activation in response to palmitate expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In pancreatic cancer cells, SP1, SP3, and SP4 regulate expression of genes involved in cell proliferation, differentiation, and migration 158 . SP1 also activates genes during the stress response 159-161 . In normal pancreas, SP1 maintains basal expression of pancreas-specific transcription factor 1 A (PTF1A) in acinar cells and vesicular glucose transporter 2 and pyruvate carboxylase in β cells 154, 156, 157 .…”
Section: Roles In the Digestive System And Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In pancreatic cancer cells, SP1, SP3, and SP4 regulate expression of genes involved in cell proliferation, differentiation, and migration 158 . SP1 also activates genes during the stress response 159-161 . In normal pancreas, SP1 maintains basal expression of pancreas-specific transcription factor 1 A (PTF1A) in acinar cells and vesicular glucose transporter 2 and pyruvate carboxylase in β cells 154, 156, 157 .…”
Section: Roles In the Digestive System And Diseasesmentioning
confidence: 99%
“…SP1 binding to the PDX1 promoter increases its activation by forkhead box A2 (FOXA2, also called HNF3B); whereas binding of SP3 to the same region reduces transactivation by HNF3B 155 . SP1 also mediates the response of β cells to lipotoxicity and acinar cells to chronic alcohol exposure 159-161 .…”
Section: Roles In the Digestive System And Diseasesmentioning
confidence: 99%
“…In addition to the proteins discussed here, other transcription factors such as Sp1, NF-kB, and CREB have all been shown to bind the promoter of NR4A1 to modulate its expression [137,445,446]. Other binding partners also include NFAT, GATA4, SRC-2, and c-JUN [77,[447][448][449]].…”
Section: Discussionmentioning
confidence: 92%
“…Studies from our lab have demonstrated that knockdown of the transcription factor ZNF148 rapidly induces differentiation in LHCN cells, suggesting that ZNF148 plays an inhibitory role during myogenesis. One study has shown that ZNF148 can suppress the expression of NR4A1 by directly binding to its promoter [446]. To determine the functional significance of this inhibitory mechanism, ZNF148 was knocked down via siRNA in LHCN cells which resulted in the rapid formation of myotubes by Day 2 (A-D) HSMM were transfected with 10 nm NT and siNR4A1 prior to differentiation for 5 days.…”
Section: Znf148 Knockdown Induces Differentiationmentioning
confidence: 99%
See 1 more Smart Citation